Baseline Findings in the Retrospective Digital Computer Analysis of Keratoconus Evolution (REDCAKE) Project. Issue 2 (February 2021) - Jiménez-García, Marta; Ní Dhubhghaill, Sorcha; Koppen, Carina; Varssano, David; Rozema, Jos J.
Abstract : Purpose: To present the baseline data for a large cohort of patients with keratoconus enrolled in the Retrospective Digital Computer Analysis of Keratoconus Evolution (REDCAKE) study. Methods: Eight centers contributed the Scheimpflug tomographical data for 906 patients with keratoconus, 743 measured with a Pentacam and 163 with a Galilei. The stage of keratoconus at baseline, the location of the reference points, minimum pachymetry (Pmin ), and maximum keratometry (Kmax ) were analyzed. The intereye asymmetry was evaluated for Kmax (anterior and posterior), Pmin, and keratoconus stage. Average maps and elevation profiles were calculated for each degree of keratoconus. Results: Keratoconus was more frequently diagnosed in men (73%) than in women (27%). At baseline, 500/1155 eyes (43%) presented with moderate to severe changes in the posterior surface, whereas moderate/severe changes were only found in 252 and 63 eyes when evaluating anterior surface and pachymetry, respectively. The location of Pmin was usually inferotemporal (94% OD and 94% OS), while the location of Kmax showed more variability and significantly higher distance from apex ( P < 0.05). The keratoconus presentation was chiefly asymmetric for all the parameters studied. Clear differences between stages could be identified in the maps and elevation profiles. Conclusions: The staging map set presented can be used as a graphical guidance to classify keratoconus stage. Keratoconus presented asymmetrically, and generally the posterior surface was more affected than the anterior surface or the thickness. Asymmetry is playing a role in KC detection. Although Pmin was almost invariably located inferotemporally, Kmax location showed higher variability and distance from the apex. Abstract : Supplemental Digital Content is Available in the Text.